(untitled) (INTERNATIONAL CONFERENCE ON ANALYSIS OF MATHEMATICS AND EXACT SCIENCES, 2024)
the mining industry is one of the most technologically complex and dangerous areas of activity, in which the safety of employees plays an important role. In this article, we will consider approaches to mathematical modeling based on extrapolation analysis of personnel safety in underground mines, which is a modern means of efficiently managing risks and ensuring labor safety. Assessment and security in the mining industry is an important task that requires a comprehensive approach. The article examines various mathematical modeling methods aimed at extrapolating current safety indicators to analyze them and predict future events. The study involves the development of mathematical models taking into account various factors affecting employee safety in mines